82 Treatment escalation plans – supporting individualised care. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Dorman, Saskie; Wilson, Rebekah Wetherly; Hasnaoui, Gemma; Hunt, Clive; Jackson, Simon
Abstract : Background: Failure to plan and document an appropriate ceiling of care can lead to treatment decisions being made urgently, out of hours, by a team unfamiliar with the patient; unwanted hospital admissions; investigations and treatments which do not contribute positively to the individual's experience of care. To address this, we developed an electronic Treatment Escalation Plan (TEP) as part of the Electronic Patient Record. TEPs were implemented trust-wide in July 2015. This is part of a wider project to improve end of life care: Poole Hospital is part of 'Building on the best' in partnership with NCPC, Macmillan, and locally funded by Forest Holme Hospice Charity. Methods: Electronic notes review of 40 consecutive adult inpatients who died within 100 days of hospital admission (index admission October 2015), using a standardised proforma (documentation of TEP or DNACPR, involvement of patients and families in discussions during the index admission). Run chart of TEP documentation showing how many electronic TEPs are created in EPR each month. Comparison with in–hospital mortality review in which notes of people who have died are reviewed by senior clinicians. Results: Of 40 patients, 17 died during the index admission, with documented discussion of prognosis for 88%, electronic TEP for 29%, DNACPR for 100%. Of 23 who died subsequently, discussion of prognosis had been documented in the index admission for 17%, electronic TEP for 4%, DNACPR for 30%. There has been a significant increase in the median number of TEPs created: 44 per month (2015/16) to 140 per month (2016/17). In 2017, 90% of adults dying in hospital have a documented ceiling of care. Conclusion: Treatment escalation plans are one way to improve decision making and documentation. TEPs are now widely used throughout the hospital, contributing to effective individualised care for people approaching the end of their life.